Javna varnost in zakonodajna politika v ekstremnih situacijah - Kečanović, Bećir (Pravni letopis, 2023)
The sequence of concepts in the title above symbolically expresses the relationship between natural and positive law. When extreme situations occur and even science is no longer capable of providing reliable answers, the search for solutions in this relationship begins with the idea of natural law. With the idea of natural law, public security in extreme situations is the highest law. This idea, which stems from the nature of reason and understands things that one sees with one‘s own eyes, is the starting point of the title paper. Of course, this does not mean that legislative policy in extreme situations can be based only on feelings. On the contrary, the response to extreme situations in all respects requires good preparation, an understanding of conflicting needs and the ability to make quick decisions based on more or less reliable information. The circumstances and extreme situations created by the Covid 19 pandemic are a valuable reference for discussion in this regard. The entire content of the paper is mostly the result of the round tables held as part of the Nomotechnical Days 2021 and 2023 seminars, where public security and legislative policy were the central subject of discussions on adapting the law to uncertain situations.
Keywords: ekstremne situacije; izredne razmere; naravno pravo; pozitivno pravo; zakonodajana politika